ЕДНА ОД ИЗБРАНИТЕ МАКЕДОНКИ: ПАРАШКЕВА СИРЛЕШЧОВА ОД БАНСКО - Славчо Ковилоски (Институт за македонска литература, 2019)
In the 19th century, Parashkeva Sirleshchova (Bansko, 1823 - ?) was one of the most prominent Macedonian interpreters of folklore. She was one of the most important informants of the brothers Dimitar and Kostadin Mollerov of Bansko. Taking advantage of the fact that she was gifted with exceptional hearing, the two brothers, between 1898 and 1900, wrote rich Folk material, consisting of songs, stories, various wedding and funerary customs, Easter customs, Mitrovden customs, more records on folk medicine, clothing, children's games, demology, folk meteorology etc. The collected materials were published just over half a century later, in 1955.
Keywords: Parashkeva Sirleshchova, Bansko, macedonian women’s, XIX century, folklore, improvisation, interpretation.